2008
DOI: 10.1371/journal.pone.0003772
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Reference Intervals of the Main Biochemical and Hematological Parameters in C57BL/6J, 129SV/EV and C3H/HeJ Mouse Strains

Abstract: BackgroundAlthough the mouse is the animal model most widely used to study the pathogenesis and treatment of human diseases, reference values for biochemical parameters are scanty or lacking for the most frequently used strains. We therefore evaluated these parameters in the C57BL/6J, 129SV/EV and C3H/HeJ mice.Methodology/Principal FindingsWe measured by dry chemistry 26 analytes relative to electrolyte balance, lipoprotein metabolism, and muscle/heart, liver, kidney and pancreas functions, and by automated bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
84
3
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(106 citation statements)
references
References 4 publications
13
84
3
6
Order By: Relevance
“…The mice receiving liposomal l-OHP showed significantly higher AST values than the control mice. However, the increased AST values observed in the mice that received liposomal l-OHP did not deviate from the standard values found in the literature, 18) and there was no significant difference in the ALT values among all groups. These results suggested that liposomal l-OHP does not induce hepatotoxicity.…”
Section: Effect Of L-ohp Encapsulated In Pegylated Liposomes On Kupffsupporting
confidence: 52%
“…The mice receiving liposomal l-OHP showed significantly higher AST values than the control mice. However, the increased AST values observed in the mice that received liposomal l-OHP did not deviate from the standard values found in the literature, 18) and there was no significant difference in the ALT values among all groups. These results suggested that liposomal l-OHP does not induce hepatotoxicity.…”
Section: Effect Of L-ohp Encapsulated In Pegylated Liposomes On Kupffsupporting
confidence: 52%
“…7C). These increases did not compromise mouse survival, and the levels detected were within the range of normal values for female C57BL/6 mice, considering age and the blood extraction method [58,59]. Biochemical analysis of urine showed normal results at all times for all parameters analyzed (Table 1).…”
Section: In Vivo Toxic Effects Of Dmsa-mnpmentioning
confidence: 68%
“…Even though BUN levels were slightly lower than the reference values, there were no significant differences between the saline and particle groups. Variations in normal BUN levels have been previously reported to be mouse strain-dependent (34,35,43).…”
Section: Kidney Histological Evaluation and Renal Functionmentioning
confidence: 91%
“…Toxicological biomarkers analyzed included blood urea nitrogen (BUN), albumin, alkaline phosphatase (Alk Phos), alanine aminotransferase (ALT), serum creatinine, glucose, total bilirubin, cholesterol, and total triglycerides. Normal range values for these biomarkers were obtained from the Laboratory and compared with those in the literature (34,35).…”
Section: Serum Biomarker Analysismentioning
confidence: 99%